Unraveling the Roots of Employee Turnover Intention at Bank Muamalat: Workload, Compensation, or Lack of Motivation ? - Kasprianti, Rista Puji; Mardani, Ronny Malavia; Basalamah , Muhammad Ridwan (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
The high rate of employee turnover in the banking sector, including at Bank Muamalat Indonesia in the East Java Region, poses a significant challenge for human resource management. This study aims to examine the effects of workload and compensation on turnover intention, with work motivation as a mediating variable. Utilizing a quantitative approach and an explanatory survey method, data were collected from 105 employees and analyzed using Structural Equation Modeling (SEM) with AMOS. The results reveal that workload has no significant effect on either motivation or turnover intention. This finding suggests that spiritual values and the Islamic organizational culture serve as protective factors in maintaining employee motivation and loyalty. Conversely, compensation has a negative effect on motivation and a positive effect on turnover intention, indicating a mismatch between employees’ perceptions of compensation fairness and their expectations. Furthermore, motivation was found to have a positive effect on turnover intention, suggesting that more motivated employees may have higher career ambitions and are more likely to seek opportunities outside the organization. Path analysis shows that motivation does not mediate the effect of workload on turnover intention but serves as a mediator in the relationship between compensation and turnover intention. These findings underscore the importance of strategic compensation and motivation management in human resource policies, particularly within institutions grounded in Sharia values.